2021
DOI: 10.1016/j.xplc.2021.100167
|View full text |Cite
|
Sign up to set email alerts
|

Trans-kingdom RNAs and their fates in recipient cells: advances, utilization, and perspectives

Abstract: The phenomenon and potential mechanisms of trans-kingdom RNA silencing (or RNA interference, RNAi) are among the most exciting topics in science today. Based on trans-kingdom RNAi, host-induced gene silencing (HIGS) has been widely applied to create crops with resistance to various pests and pathogens, overcoming the limitations of resistant cultivars. However, a lack of transformation technology in many crops limits the application of HIGS. Here, we describe the various fates of trans-kingdom RNAs in recipien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(31 citation statements)
references
References 108 publications
0
31
0
Order By: Relevance
“…In this sense, a different miRNAs pattern is expressed in plants with or without mycorrhizas (59,60) and during infectious process (61). In addition, fungal milRNAs have been pointed out as key elements in this inter-kingdom talk (62) and technological approaches, also for siRNAs, to increase pest tolerance in plants have been suggested (20,21). Therefore, it might be possible that fungal milRNAs would have needed to mimic plant miRNAs to enable a better fitting between two organisms belonging to two different kingdoms in a co-evolutionary process.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this sense, a different miRNAs pattern is expressed in plants with or without mycorrhizas (59,60) and during infectious process (61). In addition, fungal milRNAs have been pointed out as key elements in this inter-kingdom talk (62) and technological approaches, also for siRNAs, to increase pest tolerance in plants have been suggested (20,21). Therefore, it might be possible that fungal milRNAs would have needed to mimic plant miRNAs to enable a better fitting between two organisms belonging to two different kingdoms in a co-evolutionary process.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, an increasing number of evidences on the relevance of miRNAs in the fields of Agronomy and Food Sciences are arising. Thus, very recently, it has been pointed the potential use of miRNAs as tools to increase pest tolerance in agronomic practices (20,21). Besides, the latest evidence shows that dietary plant miRNAs can not only be absorbed in the intestine, but also be absorbed and packaged by gastric epithelial cells and then secreted into the circulatory system.…”
Section: Introductionmentioning
confidence: 99%
“…Exogenous constructs trigger the inherent RNAi system of plants, resulting in instability of the artificial RNAi construct. Moreover, a lack of transformation technology in many crop species also limits the broader application of HIGS (Zhao et al, 2021). On the other hand, public concern for the biosafety of genetically modified organisms (GMOs) complicates applications of HIGS worldwide (Wang and Jin, 2017; Arpaia et al, 2020).…”
Section: Perspectivesmentioning
confidence: 99%
“…In addition to transmitted proteins, recent studies have shown that transmitted RNAs play a vital role in the evolutionary arms race between hosts and pathogens (Zhao and Guo, 2019;Zhao et al, 2021).…”
Section: Trans-kingdom Rnaimentioning
confidence: 99%
“…To showcase our interest in promoting plant biotechnologies, we published a special issue on technology and applications in plants in 2021. In this issue, four review articles discussed cutting-edge technologies and their applications, including proximity labeling for probing molecular interactions in planta , organelle genome transformation and editing, trans-kingdom RNAi and related strategies for crop improvement, and CRISPR ribonucleoprotein-mediated genetic engineering ( Li et al., 2021a ; Zhang et al., 2021b ; Yang et al., 2021 ; Zhao et al., 2021 ). Among the five original articles in this issue, two reported on the development of new CRISPR-based genome editing tools ( Grutzner et al., 2021 ; Sretenovic et al., 2021 ); the other three reported an anther culture-based system that enables highly efficient and genotype-independent creation of transgenic and gene-edited plants from commercial barley varieties ( Han et al., 2021 ), a high-throughput micro-computed tomography (micro-CT) imaging system integrated with deep learning for extracting and analyzing rice morphological traits ( Wu et al., 2021a ), and a nanopore-based single-molecule approach for characterizing plant polysaccharides ( Cai et al., 2021 ), respectively.…”
mentioning
confidence: 99%